STRUCTURAL AND ULTRASTRUCTURAL ANALYSIS OF GERM CELLS FROM OVARIES OF FETUSES OF BUFFALOES - F. C. A. de Carvalho; E. Oba; L. da S. Leal; J. B. Siqueira; N. M. Velloso (Journal of Animal and Plant Sciences, 2012)
The objective of this research was the structural and ultra structural characterization of the oogonia, primary oocytes and preantral follicles of buffalo foetuses at different gestational stages. For this study twenty-nine female foetuses of buffaloes where gathered in a slaughterhouse for the analysis, and were divided into 3 experimental groups: foetuses of the first (G1, n = 10), second (G2, n = 9) and third (G3, n = 10) trimester of pregnancy. After obtaining the foetus fromthe pregnancy uterus, both ovaries were removed from each foetus, one of which was processed by the analysis of classical histology and the other by analysis of transmission electron microscopy. The formation of different germinal cell line was observed in the structural analysis of the ovaries during the three stages of gestation. In G1, foetuses already had oogonia in mitotic division grouped in cords and often associated with primary oocytes which, in some cases, were accompanied by surrounding somatic cells. In a more developed stage, the foetuses of G2 presented in the ovary many pre-enthral follicles completely formed, being mostly primary and secondary primordial follicles. In G3, the ovary was full of pre-enthral follicles at different stages of development, as well as enthral follicles. The ultra-structural analysis of oogonia, primary oocytes and oocytes from preantral follicles showed that such cells contained few organelles as mitochondria, endoplasmic reticulum and Golgi complex, been that the mitochondria were the most frequent observed in all stages. There was an increase in number of organelles, according to the development of the gem cells. These results indicate that the structure and ultra-structure of cells from strain germination of buffaloes are similar to those seen in cattle, as described in the literature for this species.
Keywords: buffaloes; germ cells; ovaries